KELAYAKAN USAHA POLE AND LINE DI NEGERI HATIVE KECIL KOTA AMBON - Haulussy, Ferdinan W. M. (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2019)
Skipjack (Katsuwonus pelamis) is a superior commodity of Maluku which is generally caught by pole and line. This pole and line business in Maluku, especially in Ambon is currently faced some problems including the availability of live bait, distant of fishing ground that have impact on fishing trips and operational costs. Even the investment of this business is quite large, but it is managed simply. This study aims to analyze the feasibility of pole and line fisheries business in Negeri Hative Kecil, Ambon. The survey was conducted on 5 pole and line business units and the data obtained were analyzed with 4 investment criterias. The results show that 1). The average fixed costs, variable costs and revenues of the 5 pole and line business units during the year amounted to Rp 80,566,238; Rp. 72,571,200 and Rp. 878,034,000; and 2). The five pole and line business units in Negeri Hative Kecil are feasible to be developed. The highest NPV value is the second unit, Rp 298,623,599; IRR 38.33%; B/C value 3.04 with a payback period (PP) 1.17 years.